Influence of dopant concentrations on morphological and optical characteristics of silver doped zinc oxide thin films - Nur Rasyidah, Rusli; Nur Aimi Syaqilah, Aziz; Nurul Fatihah, Norapandi; Nurjannah, Salim; Nurul Huda, Abu Bakar (Penerbit Universiti Malaysia Pahang, 2023)
Zinc oxide (ZnO) thin films are widely used in critical applications such as solar cells, sensors, photodetectors, and conductive layers. Many efforts have been made to modify the properties of ZnO through doping so that it can be used more widely in research fields. In this work, we report silver-doped zinc oxide (Ag-ZnO) thin films by varying the Ag concentrations between 0.05 and 0.25 wt.%. The samples were prepared through the sol-gel method, followed by the spin-coating technique onto glass substrates. The work aims to investigate how different Ag concentrations affect the morphological characteristics and optical properties of the prepared Ag-ZnO thin films. The spin-coated Ag-ZnO thin film thickness was controlled at three layers to ensure the adhesion of the nanoparticles. Field Emission Scanning Electron Microscope (FESEM) analysis showed that as the Ag concentration increased, the particles transitioned from spherical to flake-like morphologies with smaller grain sizes. The optical energy band gap was decreased to 3.17 eV from 3.28 eV (undoped ZnO) when the concentration of Ag was the highest at 0.25 wt.%. The findings reveal that Ag doping can tailor ZnO thin films morphology and energy band gap, expanding their potential use in optoelectronic and energy devices through enhanced surface area, catalytic activity, and light absorption capabilities.